Género, representación y nuevas tecnologías: mujeres y video en México - Pech, Cynthia (Revista mexicana de ciencias políticas y sociales, 2006)
En este artículo, se aborda la temática del video como tecnología de género. El video es el medio de creación artística que algunas mujeres están utilizando para crear lo que se puede llamar imá genes en femenino. Se hace un acercamiento al discurso feminista y los presupuestos teóricos que se han tomado para el análisis del discurso videográfico de las mujeres. Se presenta un breve análisis de los trabajos de las videastas Pola Weiss y Pilar Rodríguez.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-TV; 2-Genre et sexualité; 2-Humanités numériques; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créatrice; _Nettoyé

Corporeal Identities, Maternal Artivism: A New Decolonial Approach to the Study of Latin American Women Artists - Demori, Lara (Arts, 2019)
Stemming from Grosfoguel’s decolonial discourse, and particularly his enquiry on how to steer away from the alternative between Eurocentric universalism and third world fundamentalism in the production of knowledge, this article aims to respond to this query in relation to the field of the art produced by Latin American women artists in the past four decades. It does so by investigating the decolonial approach advanced by third world feminism (particularly scholar Chandra Talpade Mohanty) and by rescuing it from—what I reckon to be—a methodological impasse. It proposes to resolve such an issue by reclaiming transnational feminism as a way out from what I see as a fundamentalist and essentialist tactic. Following from a theoretically and methodological introduction, this essay analyzes the practice of Cuban-born artist Marta María Pérez Bravo, specifically looking at the photographic series Para Concebir (1985–1986); it proposes a decolonial reading of her work, which merges third world feminism’s nation-based approach with a transnational outlook, hence giving justice to the migration of goods, ideas, and people that Ella Shohat sees as deeply characterizing the contemporary cultural background. Finally, this article claims that Pérez Bravo’s oeuvre offers the visual articulation of a decolonial strategy, concurrently combining global with local concerns.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créatrice; _Nettoyé